TABIAT PEREMPUAN DALAM RISALAH KARANGAN ALIM AD-DAHRI - Ridwan, Ridwan (Universitas Lancang Kuning, 2021)
This analysis analyzes the Malay kitab entitled “Risalah” which is transcribed into Jawi by Ahmad bin Sulaiman Kamal from the original writing in Arabic written by Alim Ad-Dahri. The focus of this analysis is women’s characters found in the text. The text conveys ten women characters likened to animals. The knowledge about these women characters assists men to judge before marrying the women since a wife plays important role in determining a good marriage. This analysis qualitative descriptive analysis started with the process of translation from Jawi to the Latin alphabet. This analysis will contribute a lot in choosing a spouse to avoid failure in a marriage. Thus, it is needed to be socialized with the public.